An Improved Radar Emitter Recognition Method Based on Dezert‐Smarandache Theory. Issue 3 (1st July 2015) - Chen, Changxiao; He, Minghao; Li, Hongfei
Abstract : The parameters of radar emitter are fast changing in the current complicated electro magnetic environment, and the radar emitter recognition rate which used single sensor method cannot satisfied. To solve the problem, an improved radar emitter recognition method based on Dezert‐Smarandache theory is proposed, which can improve proportional conflict redistribution rule to solve fuzzy and conflicting information from radar emitter. Some examples are given to show the validity of the improved method.